2019
DOI: 10.1016/j.neuroimage.2018.10.084
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of dynamic cerebrovascular reactivity to spontaneous and externally induced CO2 fluctuations in the human brain using BOLD-fMRI

Abstract: In this work, we investigate the regional characteristics of the dynamic interactions between arterial CO2 and BOLD (dynamic cerebrovascular reactivity-dCVR) during normal breathing and hypercapnic, externally induced step CO2 challenges. To obtain dCVR curves at each voxel, we use a custom set of basis functions based on the Laguerre and gamma basis sets. This allows us to obtain robust dCVR estimates both in larger regions of interest (ROIs), as well as in individual voxels. We also implement classification … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 91 publications
3
44
0
Order By: Relevance
“…We conclude that upon CO 2 /H + stimulation the release of NO and prostanoids differs in the vessels of different parts of the brain but the initial endothelial Gα q/11 -mediated mechanism is the same. It is well described that brain areas respond differently to a hypercapnic stimulus, including negative responses that lead to hypoperfusion (56). In the brainstem, nuclei that are located very close to each other have been described to respond to CO 2 in different ways (26,(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conclude that upon CO 2 /H + stimulation the release of NO and prostanoids differs in the vessels of different parts of the brain but the initial endothelial Gα q/11 -mediated mechanism is the same. It is well described that brain areas respond differently to a hypercapnic stimulus, including negative responses that lead to hypoperfusion (56). In the brainstem, nuclei that are located very close to each other have been described to respond to CO 2 in different ways (26,(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…It is well described that brain areas respond differently to a hypercapnic stimulus, including negative responses that lead to hypoperfusion (56). In the brainstem, nuclei that are located very close to each other have been described to respond to CO 2 in different ways (26,(56)(57)(58). Collectively, all effects seem to serve the goal of removing CO 2 from the brain, with the notable exception of the brainstem (SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we were the first to parameterize a CO 2 response function (HRF CO2 ) as well as to show its spatial variability (Golestani et al, 2015) . Recently, Prokopiou et al presented an alternate method for HRF CO2 estimation, focusing on the difference between resting and task-driven HRF CO2 (Prokopiou et al, 2018) . To retroactively correct for the effect of CO 2 fluctuations on the fMRI signal, HRF CO2 is typically convolved with PETCO 2 recordings, and the result regressed out of the fMRI signal.…”
Section: Discussionmentioning
confidence: 99%
“…Bloodborne signals are signals driven by changes in the levels of dHb in the sample being imaged which in principle can be influenced by several physiological factors. Experimentally, it has been shown that variations in heart rate (HR; Shmueli et al, 2007), levels of carbon dioxide (CO 2 ; Prokopiou et al, 2019;Wise et al, 2004), breathing patterns (Birn et al, 2006), as well as arterial blood pressure (Whittaker et al, 2019) give rise to low-frequency (~0.1 Hz) fluctuations in fMRI presumably due to their effects on the levels of dHb (Caballero-Gaudes and Reynolds, 2017;Liu, 2016;Murphy et al, 2013). On the other hand, acquisition artifacts are caused by any kind of motion that forces the imaged sample to move in space or perturbs the magnetic field, as these movements have a direct impact on the acquisition process (Caballero-Gaudes and Reynolds, 2017;Liu, 2016;Murphy et al, 2013).…”
Section: Introductionmentioning
confidence: 99%